Pengaruh Product Quality, Brand Image, Dan Celebrity Endorsment Terhadap Kepuasan Pelanggan (Studi Kasus Konsumen Ghealsy Malang) - Lili Nur Indah Sari; Nur Hidayati; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract In Indonesia, the industrial sector is a major part of national economic development. One of the sectors of the business industry that is being worked on is the fashion industry. In reality, fashion models are always changing, and developing. This makes producers have to be wise in issuing products that are in accordance with the needs needed by consumers to achieve customer satisfaction. This study aims to determine how the effect of product quality, brand image, and celebrity endorsements on customer satisfaction.This study uses a quantitative approach. The population of this study is Ghealsy consumers who are in the city of Malang, East Java. The technique of collecting data is by distributing questionnaires. The sample in this study was taken by purposive sampling technique with the Malhotra formula totaling 100 respondents to Ghealsy consumers in the city of Malang. The variables in this study are Product Quality (X1), Brand Image (X2), Celebrity Endorsment (X3), and Customer Satisfaction (Y). The data analysis methods used are instrument test, normality test, classical assumption test, multiple linear analysis, and hypothesis testing, and test the coefficient of determination with the help of SPSS 20.0 software for Windows.The results showed that product quality had a significant effect on customer satisfaction, brand image had a significant effect on customer satisfaction, celebrity endorsement had a significant effect on customer satisfaction. Product quality, brand image, celebrity endorsement together have a significant effect on customer satisfaction. Keywords: Product Quality, Brand Image, Celebrity Endorsment, and Customer Satisfaction.